2019
DOI: 10.1088/2515-7620/ab3d91
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating nighttime lights and population distribution as proxies for mapping anthropogenic CO2emission in Vietnam, Cambodia and Laos

Abstract: Tracking spatiotemporal changes in GHG emissions is key to successful implementation of the United Nations Framework Convention on Climate Change (UNFCCC). And while emission inventories often provide a robust tool to track emission trends at the country level, subnational emission estimates are often not reported or reports vary in robustness as the estimates are often dependent on the spatial modeling approach and ancillary data used to disaggregate the emission inventories. Assessing the errors and uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The ODIAC nighttime light-based emission disaggregation is known to work less well in developing countries compared to developed countries, as the nightlight intensity sometime correlates poorly with human activity in developing countries [50,51]. In general, lots of low emissions in non-urban areas are missed in the light-based emission disaggregation for developing countries, and they tend to be assigned to cities instead [34].…”
Section: Comparing Odiac Emissions To Local Inventory Estimatesmentioning
confidence: 99%
“…The ODIAC nighttime light-based emission disaggregation is known to work less well in developing countries compared to developed countries, as the nightlight intensity sometime correlates poorly with human activity in developing countries [50,51]. In general, lots of low emissions in non-urban areas are missed in the light-based emission disaggregation for developing countries, and they tend to be assigned to cities instead [34].…”
Section: Comparing Odiac Emissions To Local Inventory Estimatesmentioning
confidence: 99%
“…The JRC EDGAR v6.0 (Joint Research Centre Emissions Database for Global Atmospheric Research; Crippa et al, 2020) and ODIAC (Open-Data Inventory for Anthropogenic Carbon dioxide; Oda and Maksyutov, 2011;Oda et al, 2018) inventories are wellestablished examples of global emission data products, but others have been developed (Andres et al, 1996(Andres et al, , 2016bAsefi-Najafabady et al, 2014;Nassar et al, 2013;Rayner et al, 2010;Wang et al, 2013), including some at the national/regional scale (Bun et al, 2019;Zheng et al, 2021a;Jones et al, 2021;Kurokawa et al, 2013;Meng et al, 2014). A number of these models use nighttime lights data as one input signal (or gridded population datasets, which in turn may be based on nighttime lights), though at least one study has found this is only moderately predictive (Gaughan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive information on urban land use, including urban construction and green coverage, helps planners prepare and arrange the structure of the urban transportation, water and green system, and determine the scale and directions of future urban development in urban master planning processes [3]. Moreover, crucial to the successful implementation of the Paris Agreement within the United Nations Framework Convention on Climate Change (UNFCCC) are accurate mapping and monitoring of greenhouse gases such as CO 2 [4]. Currently, fossil fuel CO 2 (FFCO2) emission is Remote Sens.…”
Section: Introductionmentioning
confidence: 99%
“…Founded on time-series satellite SAR data records consistently tracked at each pixel location, the method successfully detects and maps persistent (rather than temporary) building structures, which truly represent sustained human settlements in order to circumvent the shortfalls of the proxy indicator derived from NTL data [4], as illustrated in the case of Phan Thiết city versus the dragon fruit plantations in Bình Thuận (Figure 8). Such spatial data products of physical building structures are crucial for urban mapping applications, in particular for accurate estimations of FFCO2 emission required for the successful implementation of the UNFCCC Paris Agreement.…”
mentioning
confidence: 99%